Mud Crab (Scylla spp.) Aquaculture in the South-West Sundarbans Region of Bangladesh - Hasanuzzaman, Abul Farah Md.; Arafat, Shaikh Tareq; Huq, Khandaker Anisul (Iraqi Journal of Aquaculture, 2022)
Mud crab (Scylla spp.) aquaculture has become an important livelihood option for the coastal fisher-folks in Bangladesh. Mud crabs harvested from wild sources are traditionally fattened in pens installed in tidal rivers, ghers, and earthen ponds in Bangladesh. The study was aimed at understanding the practice and production economics of mud crab farming in the South-West Sundarbans region of Bangladesh, and was conducted in the areas namely Bagerhat, Satkhira and Khulna districts where mud crab fattening are predominately ventured. Most of the farmers fatten both male (lean) and female (gonadally immature) crabs of 100 - 180 g. The crabs are stocked at varying rate (12 - 641 g/m2), and fed at the rate of 8-10% of body weight with trash live fishes, dried fishes, snails, mollusks, and cattle viscera. The fattening for a mean cycle of 22 ± 14.34 days has the survival rate of 55 - 90%, and has the production of 0.065 ± 0.26, 0.084 ± 1.33, and 0.17 ± 3.76 kg/m2 in Bagerhat, Satkhira, and Khulna, respectively. After harvesting (mostly partial), crabs are sold at average price rate of 4.35 ± 0.45 US$/kg. The lowest production cost (3.14 US$/kg) and the better economic return (US$ 147.77) per cycle was recorded in the district of Satkhira. The mud crab fattening has hitherto been evaluated economically feasible in and around the Sundarbans region, but the production and economic efficiency can be scaled up adopting scientifically demonstrated regime of stocking, feeding, and health management. The development of crab seed hatchery, artificial feed for crab, and strongest marketing network are addressed as crux issues for the sustainability of mud crab aquaculture in Bangladesh.